PERANAN SIDIK JARI DALAM PROSES PENYELIDIKAN SEBAGAI SALAH SATU ALAT BUKTI UNTUK MENGUNGKAP SUATU TINDAK PIDANA PENCURIAN (Studi Kasus di Polres Gianyar) - Haprabu Hasibuan, Satya; Ketut Ariawan, I Gusti; Ngurah Parwata, I Gusti (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
Function of fingerprint in the identification process is as an indication evidence to find the perpetrators of crime, particularly crimes of theft. In article 184 paragraph (1) Indonesian law of criminal procedure, legal means of evidence shall be : the testimony of a witness, the testimony of an expert, a document, an indication, the testimony of the accused. Age of increasingly sophisticated led to the rise of crime and in the identification process requires an indication evidence, for example fingerprint.
Keywords: Indonesian law of criminal procedure, an indication evidence, identification proses, fingerprint.